استخدام البروستاغلاندين E1 تحت اللسان لإنهاء الحمل بثلثيه الثاني والثالث - الأيوب, جهاد; صالح, حسن; علي, سهاد (Latakia University Journal -Medical Sciences Series, 2019)
الهدف من الدراسة: تقييم فعالية وأمان إعطاء البروستاغلاندين E1 (ميزوبروستول) تحت اللسان لإنهاء الحمل. الطريقة : شملت الدراسة 82 مريضة, قسمت إلى 52 مريضة في الثلث الثاني للحمل و30 مريضة في الثلث الثالث, وأعطيت المجموعتين 50mcg تحت اللسان كل أربع ساعات (4جرعات) وجاءت النتائج: - مدة التحريض الفعال13.4±2 ساعة في الثلث الثاني للحمل و14.5± 2ساعة في الثلث الثالث. ومعدل الإسقاط أو الولادة المهبلية %50 في الثلث الثاني و% 93.33 في الثلث الثالث. أما الآثار الجانبية فكانت: - الغثيان (%1.9). التوهج (%1.9) في الثلث الثاني. - الغثيان (%3.3), التوهج (%3.3), الألم البطني (%10), فرط الاستثارة الرحمية (%3.3), تألم الجنين (%3.3) في الثلث الثالث للحمل. The objective of this study is evaluate the effectiveness and safety of sublingual administration of Misoprostol for pregnancy termination. The study included 82 patients, who were divided into two groups: 52 patients in second Trimester, and 30 patients in third trimester. The two groups used Misoprostol 50mcg sublingually every 4 hours (4 doses). The study shows that the mean duration of induction was13.4±2 hours in group 1 and 14.5±2 hours in group 2. The incidence of abortion or vaginal delivery was 50% in group1, and 93.33% in group 2 . the side effects were : Nausea (1.9%) and flashing (1.9%) in group 1 . Nausea (3.3%), Flashing (3.3%), Abdominal pain (10%), Uterine Hyperstimulation (3.3%), and Fetal distress(3.3%) in group 2 .